Maternal use of dietary supplements during pregnancy is not associated with coeliac disease in the offspring: The Environmental Determinants of Diabetes in the Young (TEDDY) study. Issue 3 (2nd March 2017) - Yang, Jimin; Tamura, Roy N.; Aronsson, Carin A.; Uusitalo, Ulla M.; Lernmark, Åke; Rewers, Marian; Hagopian, William A.; She, Jin-Xiong; Toppari, Jorma; Ziegler, Anette G.; Akolkar, Beena; Krischer, Jeffrey P.; et al.
Abstract: Perinatal exposure to nutrients and dietary components may affect the risk for coeliac disease (CD). We investigated the association between maternal use of vitamin D, n -3 fatty acids (FA) and Fe supplements during pregnancy and risk for CD autoimmunity (CDA) and CD in the offspring. Children at increased genetic risk were prospectively followed from birth in The Environmental Determinants of Diabetes in the Young (TEDDY) study. CDA was defined as having persistently positive tissue transglutaminase autoantibodies (tTGA). Diagnosis of CD was either biopsy-confirmed or considered likely if having persistently elevated levels of tTGA>100 AU. Of 6627 enrolled children, 1136 developed CDA at a median 3·1 years of age (range 0·9–10) and 409 developed CD at a median 3·9 years of age (range 1·2–11). Use of supplements containing vitamin D, n -3 FA and Fe was recalled by 66, 17 and 94 % of mothers, respectively, at 3–4 months postpartum. The mean cumulative intake over the entire pregnancy was 2014 μg vitamin D (sd 2045 μg), 111 g n -3 FA (sd 303 g) and 8806 mg Fe (sd 7017 mg). After adjusting for country, child's human leucocyte antigen genotype, sex, family history of CD, any breast-feeding duration and household crowding, Cox's proportional hazard ratios did not suggest a statistically significant association between the intake of vitamin D, n -3 FA or Fe, and risk for CDA or CD. Dietary supplementation during pregnancy may help boost nutrient intake, but it is not likely to modify the risk for the disease in the offspring.